Ytterbium and its complexes with porphyrins - V. D. Rumyantseva (Тонкие химические технологии, 2014)
The present review is devoted to the 70th element of the Periodic system and its complexes with natural and synthetic porphyrins. The ytterbium combination with porphyrin compounds, which are able to accumulate selectively in malignant tumors, led to the creation of a new class of diagnostic compounds fluorescing in the NIRregion in a "window of tissues transparency". Syntheses of Yb-complexes of various porphyrins with the use of Yb(acac)3 in several solvents and microwave radiation are considered. Electronic absorption spectra, fluorescence spectra and luminescence decay curves are given, the lifetimes of excited Yb-complexes state are measured, and the influence of chromophore aromatic fragments in macrocycle meso-positions on quantum exits values is considered. The carried out screening of more than 20 compounds allowed to choose the most perspective substance for early luminescent diagnostics – dipotassium salt of Yb(acac)-dimethoxyhematoporphyrin IX. Biological tests on tumor-carrier mice are carried out, and primary preparation accumulation in malignant tumors is shown. This compound was used also for the functionalization of composite nanoparticles consisting of gold-silver nanocages covered with mesoporous silicon dioxide. Syntheses of bis-porphyrins with different elements, application of ytterbium compounds in biomedicine, technics, chemical reactions and etc. are considered.